Addressing gender inequities: the role of an NGO school in Uttar Pradesh, India. Issue 1 (4th January 2016) - Roberts, Jennifer L.; Chittooran, Mary M.
Abstract : Purpose: – There has been an increase in the number of non-government organization (NGO) schools in India's disadvantaged communities. Since these schools often serve the most marginalized populations, it is important to understand their role in addressing educational inequities. The purpose of this paper is to examine the role of an NGO school in Uttar Pradesh, India in improving girls' education. Design/methodology/approach: – A case study methodology was utilized to identify barriers to girls' education and ways in which the NGO school is working to minimize educational inequities. Findings: – The barriers to girls' education in this study are traditional values, lack of economic opportunities, and safety concerns. The school works to minimize these inequities by providing a rigorous curriculum, teaching the students how to be good citizens, improving school facilities, and providing free school supplies. Implications – it is through better understanding the role of the NGO sector that a more complete understanding of the status of girls' education will develop. Originality/value: – This paper contributes to the literature on girls' education, but expands the conversation to include NGO schools.